2009
DOI: 10.1145/1539024.1508967
|View full text |Cite
|
Sign up to set email alerts
|

Engaging middle school teachers and students with alice in a diverse set of subjects

Abstract: This paper describes the integration of the Alice 3D virtual worlds environment into a diverse set of subjects in middle school, including the development of tutorials, example worlds and lesson plans. In the summer of 2008 our experiences with middle school teachers included three-weeks of training in Alice and guidance in the development of lesson plans. Our experiences with middle school students involved two one-week summer camps of instruction in Alice. We found both the teachers and the students strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Request permissions from permissions@acm.org. Technologies used in outreach programs include kinaesthetic activities such as Computer Science Unplugged [1], and visual programming environments such as Alice [10] and Scratch [7]. Robotics activities are very popular [3], because they reify the abstract behaviour of algorithms and programs as concrete artefacts that appeal to young people.…”
Section: Introductionmentioning
confidence: 99%
“…Request permissions from permissions@acm.org. Technologies used in outreach programs include kinaesthetic activities such as Computer Science Unplugged [1], and visual programming environments such as Alice [10] and Scratch [7]. Robotics activities are very popular [3], because they reify the abstract behaviour of algorithms and programs as concrete artefacts that appeal to young people.…”
Section: Introductionmentioning
confidence: 99%
“…From literature review we found that there is much interest in designing, building, testing and teaching with first programming environments and often the emphasis of studies is made on how effective the resulting environment is to convey computer science concepts and algorithms and at the same time how it is also fun and friendly to use, see for example [4]. There has been little, or null, attention paid to conclusive results yet we believe the preliminary data is promising and the effort worth continuing.…”
Section: Content and Claimsmentioning
confidence: 99%
“…Alice 3D has been used successfully [21], integrating computing within the context of a wide variety of subjects such as math, science, and language arts [20], and to help students understand what their future careers in computing might look like [27]. Scratch programming has also been used extensively [4,15,23], including with students with disabilities [1], urban youth [16], or particular underrepresented groups [10].…”
Section: Related Workmentioning
confidence: 99%